Multiplicity of bacteriocins obtained from natural strains of pectolytic phytopathogenic bacteria Pectobacterium carotovorum subsp. carotovorum isolated in various regions of Ukraine - Maksymenko, L.A.; Voychuk, S. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
Phytopathogenic bacteria Pectobacterium carotovorum subsp. carotovorum strains B1, B3, B4, B11, B12, B15, B16, B17, B23, B26 isolated from potato tubers grown in various regions of Ukraine with symptoms of soft rot disease are able to produce a variety of macromolecular bacteriocins (MCTV). Their killing activity against laboratory strains of P. carotovorum and Escherichia coli is studied. Pure fractions of MCTV are obtained. Electron microscopic analysis showed them to have shape of bacteriophage tails of various lengths, as well as phage capsids of various diameters. Serologically related proteins within MCTV of natural P. carotovorum strains and bacteriophage ZF-40 are detected, by using antiserum against MCTV of collection strain P. carotovorum J2 NCPPB 1744 and bacteriophage ZF-40. This fact can also be indicative of the phage nature of obtained killing particles.